E.M. Sharon, Revised Ordinances of the City of Davenport, of 1893, at 165 (1893) - (:unkn) unknown (My University, 1893)
§ 37: Prohibited selling or keeping for sale, any toy pistol or toy gun which uses fulminating or explosive caps, cartridges, or other explosive substances. Violators guilty of a misdemeanor.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES